MEDIATION SCHOOLS: DIFFERENT APPROACHES TOWARDS SOCIAL PACIFICATION (Isagoge - Journal of Humanities and Social Sciences, 2021)
In order to contribute to the academic discussion about the appropriate methods of conflict resolution, the purpose of this paper is to present the peculiarities of mediation through its historical perspective and main points of relevance in Brazilian legislation. In addition, doctrinal aspects about the three main schools of mediation will be presented -Harvard’s School, Circular-Narrative Approach and Transformative Mediation - demonstrating the importance of theoretical basement in the mediator’s performance, as well as the correct appliance of the tools in a determined conflictual situation. To this end, the bibliographic research methodology will be adopted using textual productions from precursors and academic scholars on the subject.